Clinical Spectrum of Atopic Dermatitis in Pediatric Age Group from a Tertiary Care Center in India: A Cross-sectional Study - Vibhu Mendiratta; Damini Verma; Himadri (Wolters Kluwer Medknow Publications, 2024)
Introduction: Atopic dermatitis (AD) is a chronic, inflammatory, relapsing skin disorder with early age of onset in infancy and early childhood. A gradual increase in the prevalence of AD has been observed recently, especially in low-income countries like ours. Objective: We aimed to study the epidemiology and clinical profile of AD among pediatric age group in a tertiary care hospital in North India. Materials and Methods: A hospital-based cross-sectional study was conducted over 1 year in the department of dermatology and sexually transmitted diseases in a tertiary care center in India. All children diagnosed with AD, aged 0-18 years, were recruited, and their clinical and demographic data were recorded. Results: In the 62 children having AD, the mean age was 7.7 ± 6.3 years. Majority of children belonged to the age group of 1-5 years. The mean age of onset of AD was 2.3 ± 2.2 years. A personal history of atopy was present in 53.2% of children, whereas 48.3% of children had a family history of atopy. Acute AD was the most common clinical type that was noted in 43.5%. Hyperlinearity of palms, keratosis pilaris, pityriasis alba, and periorbital darkening were found in 59.6%, 33.8%, 24.1%, and 29% of children, respectively. Conclusion: The prevalence of AD is low in developing countries like India, but it is slowly rising due to rapidly evolving urbanization and environmental changes. Disease manifestation is usually mild to moderate in Indian patients; hence, vigilant eyes and high clinical suspicion are required for accurate diagnosis and efficient management of AD in Indian settings.